Prevalence of antibody against rabies among confined, free‐roaming and stray dogs in a transit city of Nigeria (2011)
The prevalence of anti‐glycoprotein antibodies against rabies virus is studied in the sera of confined, free‐roaming and stray dogs in Ilorin, the capital city of Kwara State, Nigeria. A quantitative indirect enzyme‐linked immune-sorbent assay (i‐ELISA) was used to detect rabies virus anti‐glycoprotein antibodies in sera from 116 confined, 61 free‐roaming, and 13 stray dogs. The sera were collected between June and December 2008 from apparently healthy dogs. Of these 190 dogs, 81 (42.6%), consisting of 57 confined (49.1%), 23 free-roaming (37.7%) and 1 stray (7.7%), had antibody titres that exceeded the positive threshold of 0.5 equivalent units (eu)/ml against rabies, while 109 (57.4%) presented titres that were below the threshold. Prevalence of rabies anti‐glycoprotein antibody was higher in the confined dogs compared to free‐roaming and stray dogs. Our results indicated low anti‐rabies sero-prevalence (42.6%) in the dog population of Ilorin, a transit city that lies between northern and southern Nigeria. This is the first community‐based prevalence report on the anti‐rabies serological profile of dogs in Nigeria. The need for primary and booster mass vaccination of dogs and the impact of these findings on rabies control in Nigeria are discussed.